Water mass circulation and weathering inputs in the Labrador Sea based on coupled Hf–Nd isotope compositions and rare earth element distributions - Filippova, Alexandra; Frank, Martin; Kienast, Markus; Rickli, Jörg; Hathorne, Ed; Yashayaev, Igor M.; Pahnke, Katharina (Geochimica et Cosmochimica Acta, 2017)
ISSN:0016-7037 ISSN:1872-9533